Pertimbangan Hakim Terhadap Putusan Pelaku Tindak Pidana Narkotika (Studi Putusan No 359/Pid.Sus/2021/PN Ktp) - Pijar Putra Pratama (Universitas 17 Agustus 1945 Samarinda, 2023)
This writing aims to find out about the judge's consideration of narcotics offenders (study of decision No. 359/Pid.Sus/2021/PN Ktp) and to find out about the purpose of punishment for narcotics offenders. The research method is normative juridical with data analysis through a qualitative approach, using secondary data sources consisting of three parts, namely primary, secondary, and tertiary legal materials, with literature study data collection techniques. According to the results of the research and the judge's consideration in Ketapang Court Decision No. 359/Pid.Sus/2021/PN Ktp, the judge gave a lenient sanction of imprisonment for 2 years against the drug recidivist without considering the evidence owned by the defendant, and the judge did not consider the aggravating circumstances, so that the judge's decision was considered not to provide justice and benefits for both the defendant and the community and did not achieve the objectives of punishment.